Super‐resolution track‐density imaging of thalamic substructures: Comparison with high‐resolution anatomical magnetic resonance imaging at 7.0T. Issue 10 (14th November 2012) - Calamante, Fernando; Oh, Se‐Hong; Tournier, Jacques‐Donald; Park, Sung‐Yeon; Son, Young‐Don; Chung, Jun‐Young; Chi, Je‐Geun; Jackson, Graeme D.; Park, Chan‐Woong; Kim, Young‐Bo; Connelly, Alan; Cho, Zang‐Hee
<x xml:space="preserve">Abstract</x> The thalamus is one of the most important brain structures, with strong connections between subcortical and cortical areas of the brain. Most of the incoming information to the cortex passes through the thalamus. Accurate identification of substructures of the thalamus is therefore of great importance for the understanding of human brain connectivity. Direct visualization of thalamic substructures, however, is not easily achieved with currently available magnetic resonance imaging (MRI), including ultra‐high field MRI such as 7.0T, mainly due to the limited contrast between the relevant structures. Recently, improvements in ultra‐high field 7.0T MRI have opened the possibility of observing thalamic substructures by well‐adjusted high‐resolution T1‐weighted imaging. Moreover, the recently developed super‐resolution track‐density imaging (TDI) technique, based on results from whole‐brain fiber‐tracking, produces images with sub‐millimeter resolution. These two methods enable us to show markedly improved anatomical detail of the substructures of the thalamus, including their detailed locations and directionality. In this study, we demonstrate the role of TDI for the visualization of the substructures of the thalamic nuclei, and relate these images to T1‐weighted imaging at 7.0T MRI. Hum Brain Mapp 34:2538–2548, 2013. © 2012 Wiley Periodicals, Inc.